2016
DOI: 10.1080/10810730.2016.1245801
|View full text |Cite
|
Sign up to set email alerts
|

Third-Person Effect and Pandemic Flu: The Role of Severity, Self-Efficacy Method Mentions, and Message Source

Abstract: Within the context of a pandemic flu, this experiment investigated whether source (government officials or physicians), severity condition (high or low), and mention of self-efficacy method (mention present or absent) in H1N1 health news affected participants' (a) perception of media influence on self and others and (b) intentions to get vaccinated. Results found support for third-person effects, and the magnitude of the effects grew with social distance. Main effect of source, as well as interaction effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…Then, at the level of public society, Aldarhami et al [ 35 ] conducted a survey indicating that the high level of public awareness affects social distancing implementation. Besides, public health authorities and experts alike pointed out that mass media and information played an important role in developing public awareness and constructing social distancing behaviors among social populations [ 36 ]. Lastly, from the perspective of individual behaviors and psychological factors, OConnell et al [ 1 ] reported that more antisocial individuals may pose a health risk to the public and engage in fewer social distancing regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Then, at the level of public society, Aldarhami et al [ 35 ] conducted a survey indicating that the high level of public awareness affects social distancing implementation. Besides, public health authorities and experts alike pointed out that mass media and information played an important role in developing public awareness and constructing social distancing behaviors among social populations [ 36 ]. Lastly, from the perspective of individual behaviors and psychological factors, OConnell et al [ 1 ] reported that more antisocial individuals may pose a health risk to the public and engage in fewer social distancing regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Details of these criteria are given in Table 1. Economic Conditions (criterion 1) [22], [23] Technological Infrastructure (criterion 2) [24], [25] Capacity of health system (criterion 3) [26], [27] Production Capacity (criterion 4) [28] Social (Dimension 2) Population (criterion 5) [29], [30], [31] Social Distance (criterion 6) [32], [33] Tendency of Obeying Rules (criterion 7) [34], [35] Density of elderly people and chronic diseases (criterion 8) [36], [37] As can be seen from Table 1, the economic performance of the country is of great importance in order to effectively ght epidemic diseases. In the process of combating pandemic diseases, many different costs will arise.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the structure of the cultures of the countries shapes the awareness of the protection of social distance. In high-context cultures, context plays a more decisive role, communication is carried out in ways where indirect, non-verbal communication elements are more dominant [32]. In contrast, in low context cultures, the literal meanings of words are more prominent, communication is more direct.…”
Section: Literature On Cultural Factorsmentioning
confidence: 99%
“…Details of these criteria are given in Table 1. Economic Conditions (criterion 1) [22], [23] Technological Infrastructure (criterion 2) [24], [25] Capacity of health system (criterion 3) [26], [27] Production Capacity (criterion 4) [28] Social (Dimension 2) Population (criterion 5) [29], [30], [31] Social Distance (criterion 6) [32], [33] Tendency of Obeying Rules (criterion 7) [34], [35] Density of elderly people and chronic diseases (criterion 8) [36], [37] As can be seen from Table 1, the economic performance of the country is of great importance in order to effectively ght epidemic diseases. In the process of combating pandemic diseases, many different costs will arise.…”
Section: Methodsmentioning
confidence: 99%